Reasons for wine tourism in Bulgaria - Pereviazko, M.; Veres, Kateryna (My University, 2015)
The beauty of wine tourism is not sightseeing. Meeting people who produce this drink it is remains in the memory. Real manufacturer is in love with his work, and talk with them is very interesting. Some aesthetes prefer to stay in the castles of winemakers, to communicate with these eminent people.
Keywords: винний туризм; Bulgaria; wine tourism; Болгарія; кафедра туристичного та готельного бізнесу